The factor of industrial development problems on bamboo furniture design in Malaysia: a concept paper - Abdul Hamid, Abdul Ghafur; Abd Rahman, Khairul Aidil Azlin; Ismail, Sumarni (Universal Publishers, 2018)
Purpose: The purpose of this study is to focus on analyzing the problems of development bamboo furniture design industry in Malaysia. This study will look at the design practices and issues of bamboo furniture design industry in Malaysia for future research purposes. Design/methodology/approach: This study is focused on identifying the problems (issue) of bamboo industry through design management aspect by exploring extensive literature review on the bamboo industry in Malaysia. The data are collected from journal and book to find out the main issue of design management of the bamboo industry in Malaysia. Findings: Based on the analyzed data regarding to the literature review show that four issues that can be underlined through the study. The issue in the bamboo industry in Malaysia is slow growth of production activities, low value added for bamboo furniture, low bamboo supply, and lack of interest from wood-based manufacturer to enter the bamboo-based industry. Research limitations/implications: The implication of this research is a guide to the researcher to see the real issues of bamboo furniture design environmental management among bamboo manufacturer. Generally, Malaysian bamboo furniture manufacturer group towards clear practice. Some of them have taken short steps to R & D by purchasing technology from abroad through joint venture agreements. The Malaysia-produced products with manufacturing contracts through Original Equipment Manufacturing (OEM) and Original Design Manufacturing (ODM). Malaysia as all developing countries relies heavily on imported technologies to achieve rapid industrialization. Practical implications: Through the use of implication design management practice for bamboo manufacturer can provide the attitude of the Malaysian bamboo furniture manufacturer can be positive for design management practices that contribute towards the knowledge transfer. Originality/value: This concept paper produces the issue environment of design management practice among the bamboo furniture manufacturer.